Pengaruh Leader Member Exchange, Karakteristik Pekerjaan, dan Komitmen Organisasional Terhadap Kinerja Karyawan - Alfianita Hidayatin Nafisa; Suko Priyono (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to see how much influence the leader member exchange, job characteristics, and organizational commitment have on the performance of PT. Nuclear Coating Fabric. The population in this study was taken from employees of PT. Nuclear Coating Fabric. For the sampling method used in this study using one method, namely purposive sampling, so that in this study the sample used was 100 employees. Based on the findings of this study, it shows that leader-member exchange has a negative and insignificant effect, job characteristics have a positive and significant effect, and organizational commitment has a positive and significant effect. Judging from the value of the coefficient of determination, it states that leader member exchange, job characteristics and organizational commitment have an effect of 36.1% on the performance of PT. Nuclear Coating Fabric employees.